Principles of Entrepreneurship (ENT530): Social Media Portfolio: Skin Dessert / Nur Syafika Abdul Halim - Abdul Halim, Nur Syafika (2021)
In this semester, all students taking the subject ENT530 Principles of Entrepreneurship must choose a product to sell in order to complete the social media assignment. The students have to use a social media platform which is Facebook to advertise and market their product in order to gain and attract customers into purchasing them. The product that I have chosen to sell is Skin Dessert. Skin Dessert offers products with special premium grade quality materials to treat skin problems from within and brighten the skin naturally. The founder mainly targets the teenagers who have skin problems because with a clear skin they can boost up their self-confident to communicate or approach other peoples.